THE EFFECT OF EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AND COMPENSATION AS MEDIATING ROLE - Abdul Aziez (International Journal Labs, 2022)
Human resources or employees are the most important part of a company. Employee performance can be defined as the size or level of how much employees can run the company to achieve company goals within a certain period. Good employee performance will become an increasing trend of a company. Job satisfaction is employee satisfaction with the work that has been done at the company. Based on the background, research related to the effect of employee engagement on employee performance with job satisfaction and compensation as mediating role is important because it can become knowledge and management guidelines in the company. Employee satisfaction and compensation describes that the company cannot be separated from the existence of employees. Systematically, literature review research was conducted to obtain accurate results related to